Design of mechanically-optimised lattice structures for vibration isolation - Syam, Wahyudin P.; Jianwei, Wu; Zhao, Bo; Maskery, Ian; Leach, Richard K. (2017)
In this study, we investigate the use of additively manufactured strut-based lattice structures to enhance the mechanical vibration isolation properties of a structure. Three lattice designs, inspired by the common strut-based lattice structures, are presented. Design parameters to compare the lattice structures at the design stage are proposed. Finite element modelling has been used to determine the theoretical static and dynamic mechanical properties of both the single cell and the array configuration of the lattice structures. The lattices have been fabricated by selective laser sintering and experimentally tested to compare their static and dynamic properties to the theoretical model. A comparison and correlation of the static and dynamic properties of the lattice structures to the proposed design parameters are presented.